Asexual propagation bluebush (Justicia tinctoria (Oerst.) D. N. Gibson, Fam. Acanthaceae) by cuttings - Solís, Carlos A. (2015)
The effect of indolebutyric acid concentration (0, 500, 1000 or 1500 ppm), the position of the cutting on the parent branch (basal, medial or terminal), the cuttings size (6, 10 or 14 cm), the absence or presence of leaves, and the type of substrate (river sand, coconut fiber or carbonized rice husks) on rooting of bluebush under protected environment, were evaluated. The variables were the percentage and number of buds sprouting, rooting percentage and number and length of roots. Terminal cuttings presented the highest values for all variables, except for percentage of rooting: more outbreaks (17.5), length (0.17) and number of roots (0.65) than medial and medial cuttings, which would be associated with higher speed of rooting. The highest IBA doses (1000 and 1500 ppm) induced more roots per cutting (8.40 and 9.24, respectively) than lower concentrations. There was a higher percentage of rooting with IBA at 1000 ppm (69%) than without that compound (41%). Furthermore, use of leafless cuttings led to an increase in the magnitude of each of those variables. Higher bud sprouting (96%), rooting (92%) and root length (5.1 cm) values were obtained by using river sand than with any other substrate. Cuttings of 14 cm showed consistently higher number of shoots (3.71), longer roots (3.56 cm) and in greater numbers (10.71) than the smaller ones (10 and 6 cm).